2007
DOI: 10.1111/j.1440-1843.2006.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of pleural viscosity in the differential diagnosis of exudative pleural effusion

Abstract: The pleural fluid viscosity of patients with parapneumonic, tuberculous and malignant effusions are significantly different from each other. Among these groups, tuberculous effusions had the highest viscosity, and malignant effusions from lung cancer the lowest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
5
2
Order By: Relevance
“…for 10 min, and reported that pleural fluid viscosity of malignant pleural effusions was lower than those of tuberculous and parapneumonic effusions. 18 The present results were contrary to those results and the difference may be due to the temperature at which pleural fluid viscosity was measured and the speed of centrifugation. The temperature at which measurement is performed changes the reading of blood viscosity 19 and the speed of centrifugation affects the sedimentation of cellular components.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…for 10 min, and reported that pleural fluid viscosity of malignant pleural effusions was lower than those of tuberculous and parapneumonic effusions. 18 The present results were contrary to those results and the difference may be due to the temperature at which pleural fluid viscosity was measured and the speed of centrifugation. The temperature at which measurement is performed changes the reading of blood viscosity 19 and the speed of centrifugation affects the sedimentation of cellular components.…”
Section: Discussioncontrasting
confidence: 84%
“…Yetkin et al also reported that LDH and protein in pleural fluid are lower in malignant than in infectious pleural effusions, 18 but their results differ from those of previous studies, which show no difference among exudates. 9 Although inflammation of the pleura increases the protein concentration in pleural effusions, migrating inflammatory cells may also degrade proteins.…”
Section: Discussionmentioning
confidence: 89%
“…The relationship between hemorheological variables, especially plasma viscosity and febrile neutropenia, has not been extensively investigated. It has previously been reported that plasma viscosity is valuable and can be a surrogate marker of erythrocyte sedimentation rate and the other acute-phase reactants [ 8 ]. Nevertheless, the use of plasma viscosity in clinical practice has been ignored for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Some sources indicate that the normal value of plasma viscosity is between 1.3 and 1.65 mPa.s., while others state that it is 1.10–1.30 mPa.s. at 37°C and independent of age and gender [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…The selection of fluids used to simulate transudates and exudative pleural effusions was based upon studies that describe the fluid viscosity of various types of effusion. Previous reports have documented an average viscosity of most transudates of 0.93 centipoise (cP), and mean viscosity of exudates of 92.2 cP . The approximate viscosity of saline is 0.8 cP and olive oil is 81.6 cP .…”
Section: Methodsmentioning
confidence: 99%